Anakinra Reduces Epileptogenesis, Provides Neuroprotection, and Attenuates Behavioral Impairments in Rats in the Lithium-Pilocarpine Model of Epilepsy - Alexandra V. Dyomina; Olga E. Zubareva; Ilya V. Smolensky; Dmitry S. Vasilev; Maria V. Zakharova; Anna A. Kovalenko; Alexander P. Schwarz; Alexander M. Ischenko; Aleksey V. Zaitsev (MDPI AG, 2020)
Temporal lobe epilepsy is a widespread chronic disorder that manifests as spontaneous seizures and is often characterized by refractoriness to drug treatment. Temporal lobe epilepsy can be caused by a primary brain injury; therefore, the prevention of epileptogenesis after a primary event is considered one of the best treatment options. However, a preventive treatment for epilepsy still does not exist. Neuroinflammation is directly involved in epileptogenesis and neurodegeneration, leading to the epileptic condition and cognitive decline. In the present study, we aimed to clarify the effect of treatment with a recombinant form of the Interleukin-1 receptor antagonist (anakinra) on epileptogenesis and behavioral impairments in rats using the lithium-pilocarpine model. We found that anakinra administration during the latent phase of the model significantly suppressed the duration and frequency of spontaneous recurrent seizures in the chronic phase. Moreover, anakinra administration prevented some behavioral impairments, including motor hyperactivity and disturbances in social interactions, during both the latent and chronic periods. Histological analysis revealed that anakinra administration decreased neuronal loss in the CA1 and CA3 areas of the hippocampus but did not prevent astro- and microgliosis. The treatment increased the expression level of the solute carrier family 1 member 2 gene (Slc1a2, encoding excitatory amino acid transporter 2 (EAAT2)) in the hippocampus, potentially leading to a neuroprotective effect. However, the increased gene expression of proinflammatory cytokine genes (Interleukin-1β (Il1b) and tumor necrosis factor α (Tnfa)) and astroglial marker genes (glial fibrillary acidic protein (Gfap) and inositol 1,4,5-trisphosphate receptor type 2 (Itpr2)) in experimental rats was not affected by anakinra treatment. Thus, our data demonstrate that the administration of anakinra during epileptogenesis has some beneficial disease-modifying effects.